(untitled) (Research, Society and Development, 2024)
Objective: To analyze social inequities in Brazil during a health emergency. Methodology: This is a systematic review that searched for studies in the respective databases such as Pubmed, Scopus, Cinahl, Web of Science, and The Cochrane Data Base, using descriptors in English, selected from the Medical Subject Headings- MeSH. Immediately after cataloguing, the studies were analyzed using Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) and the study sample consisted of eight articles. Results: International data reinforces that around 77% of the global population lives in families that lost income during the pandemic and that black and Hispanic individuals are more likely. In Brazil, in its respective regions, critical scenarios were noticed, such as, for example, in the north and northeast regions, the lack of goods and intensive care, excessive bureaucracy in the regulation of beds, delaying the acquisition of new beds, low coverage of the sewage service. Conclusion: Social inequities are evident as a reflection of a country’s health, social and economic policies.